Endoplasmic reticulum stress-induced CRELD2 promotes APMAP-mediated activation of TGF-β/SMAD and NF-κB pathways in esophageal squamous cell carcinoma - Su, Fangyu; Yang, Xia; Yan, Zhaoyang; Wu, Junhong; Li, Xiaoxu; Xu, Tongxin; Xu, Huanchen; Wang, Xinhao; Hu, Zhaokun; Lu, Juntao; Guo, Wei (Frontiers in Immunology, 2025)
BackgroundTumor cells experience endoplasmic reticulum (ER) stress due to oncogene activation and stressors in the tumor microenvironment, such as hypoxia and acidosis. ER stress plays a crucial role in carcinogenesis. However, its oncogenic mechanism in esophageal squamous cell carcinoma (ESCC) remains poorly understood.MethodsThe transcriptional regulation of CRELD2 by ATF4 was investigated using a dual-luciferase reporter assay. Cellular proliferation, migration, and invasion capacities of ESCC cells were systematically evaluated through assays of MTS, colony formation, wound healing, transwell invasion, and flow cytometry analysis. To elucidate the molecular mechanisms underlying CRELD2 regulation, a series of experimental approaches including immunofluorescence, qRT-PCR, Western blotting, and co-immunoprecipitation assays were performed.ResultsCRELD2 was identified as a significantly differentially expressed gene in ER-stressed ESCC cells, with its induction was mediated through the PERK-ATF4 pathway. CRELD2 exhibited oncogenic properties by enhancing ESCC cells proliferation, migration, and invasion, while also serving as a critical mediator of ER stress-regulated malignant behaviors. CRELD2 facilitated physical interaction with APMAP and promoted its cell membrane localization under ER stress. Notably, knockdown of APMAP significantly attenuated malignant phenotypes, mirroring the effects of CRELD2 depletion. Further investigations uncovered that APMAP activated TGF-β/SMAD pathway by binding to TAK1 in competition with transforming growth factor beta receptor I (TGFBR1). Concurrently, APMAP orchestrated TAK1/NF-κB signaling by enhancing TAK1 phosphorylation via facilitating the assembly of TAK1-TAB1-TAB2 ternary complexes.ConclusionsCRELD2, induced by the PERK-ATF4 pathway under ER stress, promotes localization of APMAP on the cell membrane, which subsequently triggers activation of TGF-β/SMAD and NF-κB signaling pathway, ultimately driving epithelial-mesenchymal transition and malignant progression of ESCC cells, and CRELD2 may serve as a promising therapeutic target for ESCC.